Estimation of antigen-responsive T cell frequencies in PBMC from human subjects - Broman, Karl; Speed, Terry; Tigges, Michael (Journal of immunological methods, 1996)
A new method for estimating the frequency of antigen-responsive T cells, using a cell proliferation assay, is described. In this assay, the uptake of tritiated thymidine by peripheral blood mononuclear cells which have been exposed to antigen, is measured for each well on a microtiter plate. Whereas this assay is generally used as part of a limiting dilution assay, here we estimate the frequency of responding cells using a single, carefully chosen cell density. The traditional analysis of such data uses a cut-off to separate wells which contain no responding cells and wells which contain at least one responding cell. The new method uses the scintillation count to estimate the number of responding cells for each well on the plate. We do this by fitting a two-stage model, the first stage being a Poisson model with antigen-specific frequency parameters, and the second stage a linear model with plate-specific parameters.